2021
DOI: 10.1097/j.pain.0000000000002487
|View full text |Cite
|
Sign up to set email alerts
|

Exercise combined with Acceptance and Commitment Therapy compared with a standalone supervised exercise programme for adults with chronic pain: a randomised controlled trial

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…This study is a 1‐year follow‐up of an existing RCT (Casey et al., 2022), a single‐centre, 2‐armed, parallel group, randomized controlled superiority trial conducted in the Mater Misericordiae University Hospital (MMUH), Dublin, Ireland. The study was granted ethical approval by the MMUH Institutional Review Board (Ref No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is a 1‐year follow‐up of an existing RCT (Casey et al., 2022), a single‐centre, 2‐armed, parallel group, randomized controlled superiority trial conducted in the Mater Misericordiae University Hospital (MMUH), Dublin, Ireland. The study was granted ethical approval by the MMUH Institutional Review Board (Ref No.…”
Section: Methodsmentioning
confidence: 99%
“…The strengths and limitations discussed in the previous publication (Casey et al, 2022), which reported the post-intervention and 12-week follow-up results of this trial also apply to the 1-year follow-up analysis. The broad diagnostic profile of participants is representative of the population generally attending clinics for treatment of chronic disabling pain.…”
Section: Post-intervention 12-week Follow-up 1-year Follow-upmentioning
confidence: 98%
See 1 more Smart Citation
“…(p. 229). The investigators failed to mention the efficacy of evidence-based, brief psychological treatments such as Cognitive Behavior Therapy (CBT) 35 , 36 and Acceptance and Commitment Therapy (ACT), 37 , 38 both of which have been widely investigated as effective means of reducing pain catastrophization and its sequelae. Further, they failed to mention the importance of early detection and intervention in order to optimize overall pain outcomes.…”
Section: Catastrophization and Opioidsmentioning
confidence: 99%
“…It is proposed in the literature that habit formation needs an expanded view that requires the mindfulness aspect in order to be better applied to the treatment of complex issues (Gardner, 2012;Harvey et al, 2022;Lally et al, 2011;Lally & Gardener, 2013;Robinson et al, 2022;Rothman et al, 2009). A comprehensive review of this literature across different disciplines shows that mindfulness involves deliberate and intentional focused reflection (Casey et al, 2022;Liu et al, 2021;Mitchell et al, 2021;Wong et al, 2022), which are elements that need to be incorporated into intervention that has the effective use of habit formation and automaticity (Ariyasinghe & Arachchige, 2020; Lewis et al, 2021). To establish habit formation and automaticity, it therefore requires mindful self-regulation and action planning, not just a mindless repetitive action (Fleig et al, 2013;Sniehotta, 2009;Sniehotta & Presseau, 2012).…”
Section: Introductionmentioning
confidence: 99%